The Movable Stage in Hellenistic Greek Theatres. New Documentation from Messene and Comparisons with Sparta and Megalopolis - Yoshitake, Ryūichi (Archäologischer Anzeiger, 2018)
The present paper reports new survey results on the scenery storage room and stone lines in the Messene theatre and proposes a new reconstruction of the wheeled wooden stage construction as compared with other related examples from Sparta and Megalopolis. It is proposed that the wooden proskenion and skene were prepared to run on a track set on grooves 2 m wide in the Messene and Sparta theatres. The condition of the stone lines suggests that a wooden skene was used both at Messene and Sparta. The grooved stone lines under the later proskenion wall of the Megalopolis theatre might have been used for wooden scene panels.